Evaluación nutricional de adultos mayores con el Mini Nutritional Assessment : MNA (2016)
ABSTRACT: The knowledge related to elderly people concerning feeding habits, anthropometric characteristics, and their health status, is of vital interest to governmental and private entities interested in this population, in order to design strategies that allow to develop diagnoses and action plans. Objective: To evaluate the nutritional status of a group of elderly people in the town of Güintar from the municipality of Anza in Antioquia, Colombia. Materials and methods: The following analysis were used: multivariate analysis of variance (MANOVA) with canonical contrast of orthogonal type, multiple correspondence, descriptive of one-dimensional type and frequencies of one-dimensional type, where the information gathered through a survey was analyzed according to the factors of discrimination by sex. Results: It was found that women had a higher Body Mass Index than men. In terms of food consumption, it could be seen that 66.8% of the elderly people eat three meals per day, 21.5% incorporate dairy products, legumes and fish on a regular basis, 50% like fruits and 16.7% consume more than three glasses of water a day. Conclusion: About one third of the elderly people assessed presented risk of malnutrition (more women than men) and more than 10% were malnourished (more men than women). This situation requires to rethink food policies to promote adequate nutritional status and; therefore, the health of this population group.